Characteristic of thoron (220Rn) in environment. (February 2017) - Hosoda, Masahiro; Kudo, Hiromi; Iwaoka, Kazuki; Yamada, Ryohei; Suzuki, Takahito; Tamakuma, Yuki; Tokonami, Shinji
Abstract: This paper describes importance of 220 Rn (hereafter thoron) progeny measurement for the dose estimation. Although the spatial distribution of thoron activity concentration strongly depends on the distance from wall surface as an indoor thoron source), a homogeneous distribution was expected to be observed for 212 Pb activity concentration which was one of thoron progeny. Furthermore, the mean equilibrium factor for thoron obtained by the recent measurements in several countries widely ranged from 0.008 to 0.07. Therefore the bronchial dose evaluated using the equilibrium factor and activity concentration of thoron instead of thoron progeny activity concentration may have a large uncertainty. Thus, the thoron progeny measurement should be investigated at each measurement point for the dose estimation for thoron. Highlights: It will probably bring a large uncertainty for bronchial dose if the dose will be estimated without the direct measurement of thoron progeny. The direct measurement of thoron progeny is necessary for the accurate dose estimation caused by inhalation of thoron.